Risk factors assessment of suicide cases in Punjab Pakistan & medico legal frame work shortcomings in Pakistan related to psychological autopsy -a case control psychological autopsy study - Nadir Ali, Muhammad Faheem Ashraf, Noreen Farid, Abdul Mannan Hashmi, M. Asghar Khattak, Mufassar Nishat (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Psychological autopsy in Forensic Medicine context deals with the study of medico legal factors which affected victim to commit suicide. This area of Forensic Medicine is usually rarely addressed in research all over the world and especially in the Pakistan. This study is a case control study to look for the factors and their affiliation to medicolegal frame work shortcomings in Pakistan especially related to psychological autopsy. Aim: To assess different psychological factors which has influenced the victims to commit suicide and compared with the controls who were usually next of kin of these victims. Methods: A case control autopsy study was designed to investigate the factors resultant of psychological autopsy of 100 cases in four districts (Lahore, Faisalabad, Multan & Sargodha) of Punjab , Pakistan occurring during the year 2018 to 2021. We conducted the semi structured interviews with nearly 100 living controls from the next of kin of these victims of suicide. Also a questionnaire circulated to health professional related to medicolegal shortcoming related to psychological autopsy in Punjab. Results: Stresses related to personal and social life, psychiatric illness, domestic issues of marriages and poverty were the main reasons behind all these cases. There is need of implementation of reforms in our medico legal system for arrangements of qualified personals to conduct the psychological autopsy. Conclusions: For proper assessment of risk factors, causes and precipitants of suicidal cases, a proper psychological autopsy is very important in our criminal justice system. For awareness related to mental disorders and psychiatric illness, there is need of mass campaigns to avoid suicidal deaths in community.